2003
DOI: 10.1080/07349340302258
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Fine Granular Material

Abstract: This article describes screening of fine granular materials, including minerals. The first part of the study presents a description of screening and an analysis of resulting conclusions. The second part describes screens that have been developed in Lodz Technical University labs. From a number of screens only three have been chosen and described in this article. Additionally, results of some pilot-plant-scale tests involving these screens made at Lodz Technical University are discussed. Experimental tests cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Analysis of recent research [7][8], has shown that dewatering of fine and small particles (less than 0.25 mm in size) causes the greatest difficulties, because, the products formed from them have a highly developed surface, which interacts actively with water, retains significant its amounts due to the highly developed surface of the particles and the acting capillary and electrostatic forces. The porosity and permeability of these media is usually low.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of recent research [7][8], has shown that dewatering of fine and small particles (less than 0.25 mm in size) causes the greatest difficulties, because, the products formed from them have a highly developed surface, which interacts actively with water, retains significant its amounts due to the highly developed surface of the particles and the acting capillary and electrostatic forces. The porosity and permeability of these media is usually low.…”
Section: Resultsmentioning
confidence: 99%
“…A mechanical dewatering is the cheapest and most commonly used method [7][8]. Improving the efficiency of removing moisture from fine products by mechanical methods allows to save energy consumed during their thermal bringing to the state of commercial moisture content.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of recent research (Ettmayr, Stahl, Keller, & Sauer, 2000;Wodzinski, 2003;Shevchenko, Shevchenko, & Lebed, 2016), has shown that dewatering of fine and small particles (less than 0.25 mm in size) causes the greatest difficulties, because, the products formed from them have a highly developed surface, which interacts actively with water, retains significant its amounts due to the highly developed surface of the particles and the acting capillary and electrostatic forces. The porosity and permeability of these media is usually low.…”
Section: The Tendency For Enrichment Wastes Reductionmentioning
confidence: 99%
“…A mechanical dewatering is the cheapest and most commonly used method (Ettmayr, Stahl, Keller, & Sauer, 2000;Wodzinski, 2003;Shevchenko, Shevchenko, & Lebed, 2016). Improving the efficiency of removing moisture from fine products by mechanical methods allows to save energy consumed during their thermal bringing to the state of commercial moisture content.…”
Section: The Tendency For Enrichment Wastes Reductionmentioning
confidence: 99%